2010
DOI: 10.1007/s00406-010-0127-9
|View full text |Cite
|
Sign up to set email alerts
|

Attention to emotion: auditory-evoked potentials in an emotional choice reaction task and personality traits as assessed by the NEO FFI

Abstract: Several studies suggest that attention to emotional content is related to specific changes in central information processing. In particular, event-related potential (ERP) studies focusing on emotion recognition in pictures and faces or word processing have pointed toward a distinct component of the visual-evoked potential, the EPN ('early posterior negativity'), which has been shown to be related to attention to emotional content. In the present study, we were interested in the existence of a corresponding ERP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…An early posterior negativity (EPN) for emotional compared to neutral stimuli is consistently reported in visual ERP studies, and has recently been reported in an auditory ERP study of emotion (Mittermeier, et al, 2011). Despite the fact that the EPN is a reliable finding in the field of affective psychophysiology, attempts to source localize the EPN in the visual domain are infrequent, and source localization has never been done in the auditory domain.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…An early posterior negativity (EPN) for emotional compared to neutral stimuli is consistently reported in visual ERP studies, and has recently been reported in an auditory ERP study of emotion (Mittermeier, et al, 2011). Despite the fact that the EPN is a reliable finding in the field of affective psychophysiology, attempts to source localize the EPN in the visual domain are infrequent, and source localization has never been done in the auditory domain.…”
Section: Discussionmentioning
confidence: 97%
“…Seventy of these syllables had positive/happy prosody and 70 had negative/sad prosody. The validation of these syllables has been described elsewhere (Mittermeier et al, 2011), but briefly, in this stimulus set the probability of correctly recognizing a syllable with positive prosody was 99.7%, and the probability of correctly recognizing a syllable with a negative prosody was 99.6%. All syllables were 250 ms in duration, and were presented in a pseudorandomized sequence.…”
Section: Behavioral Tasksmentioning
confidence: 99%
See 1 more Smart Citation
“…Mittermeier and colleagues [45], studied if there is an emotion-specific neural correlation between positive and negative auditory emotional stimuli and attention through auditory-evoked potentials (AEPs) and if there is a specific relationship between AEPs evoked by emotional stimuli and the personality dimension extraversion-introversion. Differing from the other studies, this work focusses on the auditory emotional stimuli to analyze the correlation between reaction times to the stimuli, evoke potentials, and personality (extraversion).…”
Section: Eeg-related Workmentioning
confidence: 99%
“…To our knowledge, there are only two ERP studies (both coming from the same laboratory) that have looked at the processing of auditory, emotion-related single words (Mittermeier et al, 2011 ; Jaspers-Fayer et al, 2012 ). In Mittermeier et al ( 2011 ) the focus was on the identification of an ERP component that would also relate to the personality dimension of extroversion-introversion.…”
Section: The Present Studymentioning
confidence: 99%